Lamb growth studiеs in Tsagaa-Uul breed (Mongolian Journal of Agricultural Sciences, 2024)
The live weight of Tsagaan-Uul male lambs at weaning, around five months of age, shows a notable increase, with male lambs gaining an average of 8.4 kg and female lambs gaining 8.2 kg. Remarkably, both male and female lambs experience a growth increase of 1.2 times during the two months following weaning. During the early stages of life, from one to three months, male lambs exhibit live weights ranging from 5.63 to 7.73 kg, while female lambs weigh between 5.41 and 6.85 kg. At separation from their mothers, typically around four to six months old, male lambs weigh between 4.07 and 4.26 kg, and female lambs range from 3.77 to 4.01 kg. In the first month post-birth, lambs experience significant growth, increasing their live weight by 168.8 to 204.7 percent. However, this growth rate notably declines starting in the second month, reducing by a factor of 2.95 to 2.97 times. After weaning, when lambs are around four to five months old, the growth rate decreases further, declining by 3.89 to 4.66 times compared to their growth at two months of age, indicating a substantial slowdown in growth intensity. Under natural grazing conditions, the live weight of Tsagaan-Uul male lambs increases at a rate of 127 to 258 grams per day, while female lambs show a daily weight gain of 98 to 201 grams during their first seven months of life. Specifically, free-grazing male lambs achieve an average daily weight gain exceeding 200 grams until they reach two months of age. However, by seven months, particularly in the first ten days of September, their daily weight gain decreased by 2.03 to 2.05 times compared to the rate observed in the first month.